ICT systems security and privacy protection : 33rd IFIP TC 11 International Conference, SEC 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, proceedings /: 33rd IFIP TC 11 International Conference, SEC 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, proceedings. (2018) - Unknown
No abstract available